Associations of Parenting Style and Resilience With Depression and Anxiety Symptoms in Chinese Middle School Students - Qiu, Zhihai; Guo, Ying; Wang, Jun; Zhang, Hongbo (Frontiers in Psychology, 2022)
Background: Parenting style and resilience are independently associated with symptoms of depression and anxiety. However, no study has tested the interaction effects between the patterns of parenting style and resilience on mental health in adolescent populations. Therefore, this study aimed to explore the interaction effects between the patterns of parenting style and resilience on depression/anxiety symptoms among middle school students in China. Methods: A sample of 2,179 Chinese middle school students were included in this study. Latent profile analysis (LPA) was used to examine parenting style patterns. Multivariable logistic regression was used to analyze the associations of different parenting patterns and resilience with depression/anxiety symptoms, as well as the interaction effect. Results: LPA results showed that the most suitable model included three-profile solution, which were labeled as positive parenting, negative parenting, and moderate parenting. Subsequent analyses indicated that students across profiles exhibited significant differences in their depression/anxiety symptoms. Specifically, compared to moderate parenting, negative parenting was positively associated with depression/anxiety symptoms, while positive parenting was negatively associated with these symptoms. Moreover, low levels of resilience were positively associated with depression/anxiety symptoms compared to a high level of resilience. Although the interaction effect was not significant, there were differences in the associations between different parenting patterns and symptoms of depression and anxiety when stratifying resilience. Conclusion: The present study identified three-profile solution of parenting styles among Chinese middle school students using LPA as a person-centered approach. Future interventions targeting depression/anxiety symptoms in adolescents may consider the potential influence of patterns of parenting styles, or improved resilience, to achieve better intervention outcomes.